Attitudes About Sexual Activity Among Postmenopausal Women in Different Ethnic Groups: A Cross-sectional Study in Jahrom, Iran - S Jamali; Sh Javadpour; L Mosalanejad; R Parnian (JRI, 2016)
Background: Sexual function is affected by personal and interpersonal factors, familial and social traditions, culture, religion, menopause, and aging. So, ethnicity is a determining factor in sexual function. The present study aimed to investigate the prevalence of sexual dysfunction and attitudes towards sexuality in postmenopausal women among three different ethnic groups in Iran. Methods: This cross-sectional study was conducted on 746 postmenopausal women between 50 and 89 years who referred to Honoree clinic, Jahrom in 2013. Among the study participants, 42.4% were Arab, 33.5% were Persian, and 24.1% were Lor. Data were collected about women’s socio-demographic characteristics, attitudes regarding sexuality and sexual function. The descriptive statistics were used for demographic variables. Moreover, ANOVA, post hoc (LSD) was used. Besides, p<0.05 was considered statistically significant. Results: The participants’ mean age was 60.10±6.89 years and the total mean score of Female Sexual Function Index (FSFI) was 19.31±8.5. In addition, 81.5% of the women had sexual dysfunction (FSFI <26.55) and only 147 women (18.5%) had normal sexual function (FSFI >26.55). Sexual dysfunction was 75.3% in Arabs, 83.2% in Persians, and 86.1% in Lors. Besides, the most prevalent sexual dysfunction was dyspareunia in Arabs and arousal disorder in Persians and Lors. Conclusion: The results of this study showed that sexual dysfunction is considerable among postmenopausal women. The most prevalent sexual dysfunction was dyspareunia in Arabs and arousal disorder in Persians and Lors.